Covid-19 Infection, Pregnancy Outcomes and Maternal & Neonatal Complications - Monika, Ishrat Saba Mari, Bharat Kumar Maheshwari, Kulsoom, Monika Maheshwari, Qararo Shah Syed (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Covid-19 infection potentially affects pregnancy, its outcomes and may lead to maternal and neonatal complications. Objective: To investigate and compare the pregnancy outcomes and feto-maternal complications among covid-19 infected and non-infected women. Study Design: Prospective study. Setting: Shaikh Zaid Women Hospital, Shaheed Mohatarma Benazeer Bhutto Medical University, Larkana. Duration: From August 2021 to February 2022. Material and Methods: A sample of 204 pregnant women of age 18-50 years was taken and sorted as either having covid-19 (n= 90) or without covid-19 (n= 114). They presented in 3rd trimester with single fetus. Exclusion criteria were having haemoglobinopathy, malpresentation, placental abruption or other pregnancy risks. The rt-PCR used to test infection status. Data collected through a pre-designed questionnaire and analyzed through SPSS Version-25. Results: The maternal age ranged between 28 to 39 years with a mean ± SD age of 30.3 ± 6.66 which did not differ in two groups. Lower gestational age was of the covid-19 infection group i-e; 34.75 ± 1.54 weeks then covid-19 negative (37.01 ± 2.14 weeks; p value < 0.001). Most common covid-19 symptoms were fever at admission (79%) dry persistent cough (51%), malaise (21%) and dyspnea (22%). More caesarean sections (52.22%; n = 47) in covid-19 +ve group noted than covid-19 negative (34.21%; n = 39). PIH, preeclampsia/ eclampsia, preterm labor, infections which needed antibiotics therapy and referral for higher dependency care (p values = 0.059, 0.003, 0.893, 0.179 and 0.002 respectively) and preterm birth, LBW, SGA, fetal distress, admission for neonatal rususciation/ ICU and fetal death (p values = 0.433, 0.136, 0.877, 0.79 0.436 and 0.428 respectively) were more frequent among covid-19 positive group. Conclusion: Pregnancy with convid-19 face relatively more unwanted outcomes, maternal and neonatal complications compared to the covid-19 negatives. Antenatal and full range of obstetric and medical care of such cases is highly recommended to achieve better outcomes.